Institutional Cash Pools and the Triffin Dilemma of the U.S. Banking System - Pozsar, Zoltan (IMF Working Papers; Working Paper ;, 2011)
Through the profiling of institutional cash pools, this paper explains the rise of the "shadow" banking system from a demand-side perspective. Explaining the rise of shadow banking from this angle paints a very different picture than the supply-side angle that views it as a story of banks' funding preferences and arbitrage. Institutional cash pools prefer to avoid too much unsecured exposure to banks even through insured deposits. Short-term government guaranteed securities are the next best choice, but their supply is insufficient. The shadow banking system arose to fill this vacuum. One way to manage the size of the shadow banking system is by adopting the supply management of Treasury bills as a macroprudential tool.